Етнокультурні процеси у пізньому палеоліті та проблема епіграветту - Залізняк, Л.Л. (Археологія, 2000)
Стаття присвячена визначенню та палеоетнологічній інтерпретації такого складного явища пізнього палеоліту Центральної та Східної Європи як епіграветт. Значущість цієї проблеми для вітчизняного палеолітознавства стає зрозумілою, якщо зважати на те, що більшість пізньопалеолітичних крем'яних комплексів з території України, за типологічними ознаками, належить саме до цієї культурної спільноти. Статья посвящена определению и палеоэтнологической интерпретации такого сложного явления позднего палеолита Центральной и Восточной Европы как Эпиграветт. Большинство известных позднепалеолитических кремниевых комплексов территории Украины типологически являются эпиграветтскими. К числу последних автор относит коллекции, которые датируются периодом 20—10 тыс. лет назад, в микронаборе которых доминируют микроострия, треугольники и прямоугольники с притупленной спинкой величиной до 4 см.
Эпиграветтская общность являла собой один из крупных блоков первобытной этнокультурной непрерывности, которые возникли в позднем палеолите как древнейшая форма этнической дифференциации человечества в связи с распространением экзогамии. Нарастание этнокультурной специфики отдельных регионов, усугубленное природно-ландшафтной дифференциацией приледниковья на рубеже плейстоцена и голоцена, привело к распаду эпиграветта и других блоков первичной этнокультурной непрерывности на классические археологические культуры поздней первобытности, которые являют собою следы первобытных этносов финального палеолита, мезолита, неолита, бронзы и раннежелезного века. The paper is devoted to the definition and pateo-ethnological interpretation of such a complex phenomenon of the Late Paleolithic Age of Central and East Europe as epigravett. In Ukraine’s territory, most known late-paleolithic flint complexes are epigravettic typologically. Lastly, the author refers to the collections dated by the period of 20—10 thousand years ago, whose micro sets are dominated by micro points, triangles, and rectangles with blunt backs up to 4 cm in size.
The epigravettian community presented itself as one of the large blocks of the primeval ethnocultural continuity, which arose as the most ancient form of ethnic differential of humanity in the Late Paleolithic Age in connection with the expansion of exogamy. A growth of the ethno-cultural specificity of separate regions, which was intensified by the natural-landscape differentiation of the near-glacier area at the boundary of Pleistocene and Holocene, caused the decay of epigravett and other blocks of the primary ethnocultural continuity into classical archeological cultures of the late primitiveness, which are the traces of primeval ethnic community in the Final Paleolithic, Mesolithic, Late Stone, Bronze, and Early Iron Ages.